DEVELOPING TASK-BASED ENGLISH MATERIALS MODEL FOR STUDENTS OF PRIMARY TEACHER EDUCATION - Ridawati Sirait; Audi Yundayani; Didik Santoso (SOSCIED, 2022)
English can be used as the language of instruction in specific educational units to support students' foreign language skills. However, teachers are still not fit to teach lessons in English because of the poor quality of English. This study aims to develop a model of task-based English materials for students of primary teacher education. The type of this study is Research and Development through the model of task-based. This study involved alumni, English lecturer of PGSD UNIMED, and students of PGSD UNIMED as the research’s participants. Questionnaire, interview guidelines, and English test were the instruments used to collect the data. The research findings show that (1) from the analysis result, 100% respondents wanted primary school books based on existing themes in content courses would be used as sources of course materials; 2) the design used task-based approach and was made based on basic competency to measure the student competency achievement; (3) the basic competence for unit one is to represent and communicate observations and ideas in a variety of ways; (4) according to experts judgment, the developed materials are suitable for students of primary teacher education, which can be shown from the percentage of the content and language appropriateness are 100%, presentation appropriateness is 97% and layout appropriateness is 95% which categorized as very good; (5) there are differences in test results before and after the explanation of English teaching materials. It means that the English teaching materials developed is effective in increasing students' interest in learning.